Astaxanthin activates the Nrf2/HO-1 pathway to attenuate indoxyl sulfate-induced oxidative stress and DNA damage in renal tubular epithelial cells - Qian, Xiaoli; Wang, Zhixia (Frontiers in Pharmacology, 2026)
Astaxanthin (AST) was investigated for its therapeutic role in chronic kidney disease (CKD) and its underlying mechanisms. Network pharmacology analysis identified 29 overlapping targets of AST and CKD, which were enriched in oxidative stress-related pathways, particularly the Nrf2/HO-1 axis. Molecular docking further confirmed stable binding of AST to hub proteins such as HMOX1, SOD2, and NOS2. In vitro, indoxyl sulfate (IS)-treated HK-2 cells were used to establish a CKD injury model. Cell viability was assessed by MTT assay, apoptosis by TUNEL staining and Western blotting, oxidative stress by ROS detection and measurement of glutathione (GSH), superoxide dismutase (SOD), and malondialdehyde (MDA). DNA damage was evaluated by alkaline comet assay and γH2AX expression, while cellular senescence was examined by SA-β-galactosidase staining and p53/p21 expression. IS exposure significantly increased apoptosis, oxidative stress, DNA damage, and senescence, while reducing cell viability, antioxidant capacity, and nuclear Nrf2 expression. AST treatment effectively reversed these changes, improving cell viability and antioxidant defenses, and alleviating apoptosis, ROS accumulation, DNA damage, and senescence. These integrated computational and experimental findings indicate that AST exerts renoprotective effects through coordinated modulation of multiple oxidative stress–related pathways, primarily via activation of the Nrf2/HO-1 signaling axis.